The Role of Social Media in Providing New Opportunities in Work and Life: A Qualitative Study of Professional Saudi Arabian Women - Saleh, Ramzia Hisham (Université d'Ottawa / University of Ottawa, 2020)
This study builds on a small but growing body of research concerning socio-economic, cultural, political, and personal challenges influencing Saudi women’s professional development. Although Saudi women have more advantages and opportunities in 2020 compared to previous historical periods, women still face challenges related to employment and professional status. This research provides an in-depth analysis of the insider experience connected to challenges Saudi women face in work and life that hinder their professional development. Specifically, this research explored the role of social media in providing new opportunities to help Saudi women overcome challenges they face in work and life. Guided by a qualitative approach, this interpretive study is conducted through interviews, supporting documents analysis, and personal experiences. This study draws on Technofeminism, Intersectional Feminism, and Social Role Theory in order to provide a broad theoretical lens to help interpret findings. Using thematic analysis, six main themes were uncovered: (1) socio-cultural challenges, (2) personal challenges, (3) ethical challenges, (4) institutional challenges, (5) civic and professional engagement, and (6) socialization and privacy issues. General findings indicated that despite efforts from the Saudi Arabian government to enhance women’s rights in society, women continue to face socio-cultural, personal, and ethical challenges in work and life. The advanced analysis revealed that social media does have a positive role in providing Saudi women with new opportunities to overcome challenges they face but that cultural norms and traditional practices continue to create challenges that hinder Saudi women’s professional development.
Keywords: Saudi women; Saudi Arabia; Culture; Social norms; Social media; Technofeminism; Intersectionality; Feminism; Professional Development; Challenges and Opportunities; Islam